Analyzing Syllabus "Sports and Pedagogical Improvement in Artistic Gymnastics" for Female Second-Year Students of the School of Physical Education and Sports - Т. М. Кравчук; Н. М. Санжарова; Ю. В. Голенкова (OVS LLC, 2016)
The objective is to analyze the syllabus content of the discipline "Sports and Pedagogical Improvement (Artistic Gymnastics)" for female second-year students of the School of Physical Education and Sports. Materials and methods: analysis, synthesis and comparison of literary sources, pedagogical observation, study and collation of instructors' positive working experience. Results. The analysis of the syllabus content of the discipline "Sports and Pedagogical Improvement" for female second-year students allowed to determine that the principal tasks are: to arm the students with the knowledge of the main types of training for qualified female athletes in artistic gymnastics; to teach the future professionals the fundamentals of the methods of physical, technical, psychological, tactical and theoretical training in artistic gymnastics; to shape the students' professional and pedagogical abilities and skills in effective realization of all types of female gymnasts' training; to cultivate in the future professionals the knowledge, abilities and skills of organizing control of the level of female gymnasts' physical, technical, psychological, tactical and theoretical training. Conclusions. Teaching the discipline "Sports and Pedagogical Improvement (Artistic Gymnastics)" in the second year of training at the School of Physical Education aims at arming the students with the knowledge of the main types of female athletes' training in artistic gymnastics; teaching them the fundamentals of the methods of physical, technical, psychological, tactical and theoretical training, and shaping professional and pedagogical abilities and skills in effective realization of all the above-mentioned types of training in the future professional activity.